The theory and technique of asıf. part ii: treatment of various fractures using asıf on fixation of plates and screws - Zeki Oğurtan; Fahrettin Alkan (Eurasian Journal of Veterinary Sciences)
In this part II, application of lag screw technique (interfragmental compression) with cancellous and cortex screws, axial compression and neutralization plate fixations with decompression plate, along with schematic fixation of various fractures, using ASIF techniques in small animals, have been outlined lo guide the veterinary surgeons.